Human rights activism and transitional justice advocacy in Northern Ireland - Bryson, Anna (International journal of transitional justice, 2023)
This article offers a critical assessment of efforts to address the legacy of the Northern Ireland conflict. We begin with an overview of government-led initiatives since 1998 and then reflect on three underpinning themes: justice, accountability and the tilt towards impunity; the shift from ‘truth’ to ‘information’ recovery; and the instrumentalization of history. We then offer a reflexive assessment of our endeavours to contribute to a ‘from below’ variant of legal, political and historical advocacy. Reflecting on our efforts to contest and critique successive government proposals, we draw out three overlapping ‘ideal types’ of transitional justice advocacy: technical engagement, coalition building and exposition. We conclude by highlighting the very specific challenges of engaging in transitional justice scholarship and advocacy in a ‘post-truth’ era.